2012 Moon Mars Analog Mission Activities on Mauna Kea, Hawai'i. Issue 10 (15th May 2015) - Graham, Lee; Graff, Trevor G.; Aileen Yingst, R.; ten Kate, Inge L.; Russell, Patrick
Abstract Rover-based 2012 Moon and Mars Analog Mission Activities (MMAMA) scientific investigations were completed at Mauna Kea, Hawaii. Scientific investigations, scientific input, and science operations constraints were tested in the context of an existing project and protocols for the field activities designed to help NASA achieve the Vision for Space Exploration. Four separate science investigations were integrated in a Martian analog environment with initial science operations planned based on a model similar to the operations control of the Mars Exploration Rovers (MER). However, evolution of the operations process occurred during the initial planning sessions and as the analog mission progressed. We review here the overall program of the investigation into the origin of the valley including preliminary sensor data results, an applicable methodology for developing an optimum science input based on productive engineering, and science trades and the science operations approach for an investigation into the valley on the upper slopes of Mauna Kea identified as "Apollo Valley".